Opioid Agonist Maintenance Treatment Outcomes—The OPTIMUS International Consensus Towards Evidence-Based and Patient-Centred Care, an Interim Report - Lucas Wiessing; Prakashini Banka-Cullen; M. Gabriela Barbaglia; Vendula Belackova; Saed A. S. Belbaisi; Peter Blanken; Patrizia Carrieri; Catherine Comiskey; Daniel Dacosta-Sánchez; Geert Dom; Venus Fabricius; Hugo Faria; et al. (Springer, 2023)
Non-medical opioid use is a major public health concern causing high mortality. While opioid agonist maintenance treatment (OMT) is a key life-saving intervention, there is (a) no international consensus on opioid treatment outcomes and (b) few opioid treatment outcome studies include key (public) health outcomes, such as overdose or HIV/hepatitis C. We report the rationale and study protocol for, and preliminary results of, an on-going international OMT outcomes consensus study that aims to address this double gap (n = 110 collaborating experts from 32 countries, plus a n = 477 Delphi evaluation panel from 26 of those countries: 58% male, 41% female; 47% OMT patients, 53% OMT professionals). We present a first draft of a patient interview guide (including a ‘clinical form’) to monitor OMT outcomes in six domains. The form appears to be well accepted and feasible in early testing. Through this, we aim to enhance the quality of and access to OMT and improve the survival, health, and quality of life of people who use opioids, while promoting non-stigmatising patient-physician relationships.